Ambivalensi Politik Digital: Algoritma, Gamifikasi, dan Polarisasi Generasi Z di TikTok - Purboyo, Muhammad Guntur; Amriwan, Azis; Junaidi, Junaidi; Tivantara, Branden Jaya; Putra, Hanif Dinanda (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2025)
TikTok has become a primary platform for Generation Z's political information consumption. The algorithmic mechanisms of the For You Page and live battles, combined with in-app gift features, create a unique dynamic where entertainment merges with political partisanship. This phenomenon shows that polarization is not only a result of algorithmic filters but also of digital rituals full of symbols and emotions. This article explains how TikTok's algorithms and gift features operate as social mechanisms that limit informational diversity and reinforce political polarization among Generation Z. Using a qualitative approach, the study conducted a thematic analysis of political live battle videos and in-depth interviews with eight Generation Z participants (18-24) in Bandar Lampung. The analysis highlights algorithmic curation patterns, the dynamics of gift-giving, and Generation Z's perceptions of political content. The study found that partisan content dominates live battles, with large gifts given by pro-candidate accounts as political support, while small gifts are used by ordinary viewers. Participants watched these battles more for entertainment than for information, yet they were consistently exposed to political partisanship. The findings demonstrate that TikTok's algorithm and gift economy jointly construct a digital political space based on emotion and symbols rather than substantive discussion. This study confirms that Generation Z's political polarization is rooted in both algorithmic curation and the logic of digital entertainment mobilized by political supporters.